2021
DOI: 10.3390/ijms222313117
|View full text |Cite
|
Sign up to set email alerts
|

Protocadherin-7 Regulates Osteoclast Differentiation through Intracellular SET-Binding Domain-Mediated RhoA and Rac1 Activation

Abstract: Protocadherin-7 (Pcdh7) is a member of the non-clustered protocadherin δ1 subgroup of the cadherin superfamily. Although the cell-intrinsic role of Pcdh7 in osteoclast differentiation has been demonstrated, the molecular mechanisms of Pcdh7 regulating osteoclast differentiation remain to be determined. Here, we demonstrate that Pcdh7 contributes to osteoclast differentiation by regulating small GTPases, RhoA and Rac1, through its SET oncoprotein binding domain. Pcdh7 is associated with SET along with RhoA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…We also cannot exclude the possibility that PCDH7 suppresses myosin phosphatase activity by influencing Rho-ROCK modulators. A recent study reported that PCDH7 involves in the activation of Rho signaling during osteoclast differentiation (Kim et al, 2021). Further study is necessary to elucidate the molecular details of PCDH7 dependent regulation of myosin phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
“…We also cannot exclude the possibility that PCDH7 suppresses myosin phosphatase activity by influencing Rho-ROCK modulators. A recent study reported that PCDH7 involves in the activation of Rho signaling during osteoclast differentiation (Kim et al, 2021). Further study is necessary to elucidate the molecular details of PCDH7 dependent regulation of myosin phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that PCDH7 functions in osteoclast differentiation by regulating RhoA and Rac1. Loss of PCDH7 expression impairs RhoA activation in pre-osteoclasts (Kim et al, 2021). In agreement with those studies, we also observed that depletion of PCDH7 impairs active RhoA and myosin levels at the cleavage furrow.…”
Section: Discussionmentioning
confidence: 99%
“…Pcdh7 plays a crucial role in the activation of Rho-family small GTPases, RhoA and Rac1 in osteoclasts. Its intracellular domain, which is known for binding to the oncogene SET (SET/Template-activating factor 1 (TAF1)), is essential for regulating RhoA and Rac1 [20,21]. These findings provide evidence that Pcdh7 plays a role in osteoclast differentiation as a mediator of cell signaling.…”
Section: Introductionmentioning
confidence: 96%
“…The activity of PP2A and Rho-family small GTPase is reportedly linked through Glycogen synthase kinase-3β (GSK3β) in cancer cells [26][27][28]. Since Pcdh7 associates with RhoA and Rac1 through its intracellular SET binding domain and since the domain is critical for Pcdh7-mediated activation of RhoA and Rac1 during osteoclast differentiation [20], these observations suggest that PP2A plays a relevant role in Pcdh7-mediated signaling in osteoclasts.…”
Section: Introductionmentioning
confidence: 99%